Sosialisasi dan Pelatihan Budidaya Tanaman Hidroponik: Langkah Awal Menuju Pertanian Urban dengan Pemanfaatan Limbah Botol Plastik di Desa Lebo - Dela Tri Astuti Lumban Gaol; Silmi Savira Nursyamsiyah; Amanda Diva Mia Putri; Rahmadiah Indah Setyoningrum; Charles Fernando Marpaung; Fauzan Attamimi; Muhammad Dimas Aryautra Pratama; Muhammad Rizky Bagasnanta; Marchelo Boas Permata; Dhiya Fauz Wiman (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Community service activities in Lebo Village, Sidoarjo, aim to overcome the problem of narrowing agricultural land and inorganic waste by applying the wick system hydroponic method using used plastic bottles as planting media. Through socialization and practice involving PKK women, this method proved to be effective and easy to apply, allowing them to grow organic vegetables on limited land. The active participation and enthusiasm of the participants showed the potential of implementing hydroponics independently at home. However, challenges such as hydroponic fertilizer availability and plant maintenance need to be overcome with commitment and ongoing support. Thus, wick system hydroponics can positively contribute to local food security and the environment.